2018
DOI: 10.3390/genes9070358
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Medical Consequences of Archaic Introgression into Modern Human Genomes

Abstract: The demographic history of anatomically modern humans (AMH) involves multiple migration events, population extinctions and genetic adaptations. As genome-wide data from complete genome sequencing becomes increasingly abundant and available even from extinct hominins, new insights of the evolutionary history of our species are discovered. It is currently known that AMH interbred with archaic hominins once they left the African continent. Modern non-African human genomes carry fragments of archaic origin. This r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…If fixed differences with a single outgroup are unavailable (for instance if different outgroup species were used to polarize polymorphic sites), then the test can also be set up without fixed differences, by using probabilities p X ' ;n from Eq (7) in Eq (14) and p 0 X ' ;n ða; d ' ; DÞ from Eq (10) in Eq (15).…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…If fixed differences with a single outgroup are unavailable (for instance if different outgroup species were used to polarize polymorphic sites), then the test can also be set up without fixed differences, by using probabilities p X ' ;n from Eq (7) in Eq (14) and p 0 X ' ;n ða; d ' ; DÞ from Eq (10) in Eq (15).…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Well-documented examples cover a wide range of taxa, including the transfer of wing-pattern mimicry genes in Heliconius butterflies [7], herbivore resistance and abiotic tolerance genes in wild sunflowers [8,9], pesticide resistance in mice [10] and mosquitoes [11], and new mating and vegetative incompatibility types in an invasive fungus [12]. Such adaptive introgressions also occurred in modern humans [13][14][15]: local adaptation to hypoxia at high-altitude was shown to be associated with selection for a Denisovanrelated haplotype at the EPAS1 hypoxia pathway gene in Tibetan populations [16]; positive selection has been characterized for three archaic haplotypes, independently introgressed from Denisovans or Neanderthals in a cluster of genes involved in the innate immune response [17], and immunity related genes show evidence of selection for Neanderthal and Denisovan haplotypes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have brought 6 clear evidence of cross-species introgression of advantageous alleles [3-6].7 Well-documented examples cover a wide range of taxa, including the transfer of 8 wing-pattern mimicry genes in Heliconius butterflies [7], herbivore resistance and abiotic 9tolerance genes in wild sunflowers [8,9], pesticide resistance in mice [10] and 10 mosquitoes [11], and new mating and vegetative incompatibility types in an invasive 11 fungus [12]. Such adaptive introgressions also occurred in modern humans [13][14][15]: local 12 adaptation to hypoxia at high-altitude was shown to be associated with selection for a 13 July 10, 2019 2/96 Denisovan-related haplotype at the EPAS1 hypoxia pathway gene in Tibetan 14 populations [16]; positive selection has been characterized for three archaic haplotypes, 15 independently introgressed from Denisovans or Neanderthals in a cluster of genes 16 involved in the innate immune response [17], and immunity related genes show evidence 17 of selection for Neanderthal and Denisovan haplotypes [18, 19]. 18 In all examples above, evidence of adaptive introgression rests on a comparative 19 analysis of DNA from both donor and recipient species.…”
mentioning
confidence: 99%
“…These methods permit analyzing the phylogenetic relationships among closely related taxa using a multilocus approach, and the signatures of admixture (the mixing of genomes of different taxa through hybridization) and introgression (the passing of alleles from one parental population to another through hybridization and backcrossing). Several primate studies have reported introgression of neutral (e.g., baboons: Wall et al 2016;howler monkeys: Baiz et al 2018) and advantageous alleles (e.g., Neanderthal/Denisovan into modern humans: Dannemann et al 2016;Dolgova and Lao 2018;Enard and Petrov 2018;Gittelman et al 2016;Racimo et al 2015Racimo et al , 2017 as a consequence of current or ancient hybridization. In some instances, alleles of only a few genes or genomic regions have moved from one species to another, but in other cases introgression has led to the formation of lineages of hybrid origin.…”
Section: )mentioning
confidence: 99%